Summertime and the drivin' is easy? Daylight Saving Time and vehicle accidents - Ioannis Laliotis; Guiseppe Moscelli; Vassilis Monastiriotis (London School of Economics and Political Science (LSE), European Institute, 2019)
Although it is commonly understood that light conditions affect driving behaviour, detailed evidence is scarce especially for EU countries. In this paper we use the exogenous variation in daylight caused by Daylight Saving Time (DST) shifts to examine the role of light conditions on vehicle accidents. We use a rich dataset from Greek administrative data covering the universe of all types of recorded vehicle accidents over the period between 01 January 2006 to 32 December 2016. Relying on a regression discontinuity design we attempt to provide a casual evaluation regarding the impact of exogenous time shifts on the number of vehicle crashes. Our results are supportive of an ambient light mechanism that reduces the counts of serious vehicle accidents during the Spring transitions and increases on the count of minor ones during the Fall transition, especially during the most impacted hours within the day. We discuss the implications of our study both for the importance of light ambience conditions for car accidents and for the particular case of the adoption and preservation of DST policies.
Keywords: I12; I18; R41; 330; DST; Driving behaviour; vehicle accidents; Greece